The role of clinical and immunological parameters in predicting the effectiveness of additional immunotropic therapy in oxygen-dependent patients with COVID-19 coronavirus disease - Riabokon, O. V.; Cherkaskyi, V. V.; Riabokon, Yu. Yu.; Vynokurova, A. V.; Рябоконь, Олена Вячеславівна; Черкаський, Володимир Васильович; Рябоконь, Юрій Юрійович; Винокурова, А. В. (Запорізький державний медико-фармацевтичний університет, 2023)
Aim. The purpose of the research is to find out the role of clinical and immunological parameters in predicting the effectiveness of additional immunotropic therapy in oxygen-dependent patients with the coronavirus disease COVID-19. Material and methods. 79 oxygen-dependent patients with COVID-19 were examined, who received additional therapy with tocilizumab according to current protocols. The patients were divided into groups: I group – 39 patients who recovered; group II – 40 patients with a fatal outcome of the disease. The content of ferritin (Monobind Inc., USA), interleukin (IL) IL-2 (Elabscience, USA), IL-6 (Invitrogen, Austria), monocyte chemotactic protein-1 (MCP-1) (Elabscience, USA) was determined in the blood serum of patients and persons of the control group by the method of immunoenzymatic analysis. Statistical processing of the obtained data was carried out in the program Statistica 13 for Windows (StatSoft Inc., No. JPZ804I382130ARCN10-J). Results. Threshold levels of immunological parameters at different stages of observation, which have prognostic value regarding the risk of a fatal outcome of COVID-19, have been established. After 5 days of tocilizumab administration, the preservation of the indicator of the absolute number of blood lymphocytes ≤1.2 × 109/l (AUC = 0.631, p = 0.039), CRP level >67.5 mg/l (AUC = 0.670, p = 0.020), IL-2 >309.45 pg/ml (AUC = 0.761, p = 0.013), IL-6 >4.66 pg/ml (AUC = 0.871, p < 0.001) indicated a high probability of developing a fatal outcome of the disease in patients with COVID-19. The analysis of the diagnostic significance of ferritin showed the informativeness of the level of its increase as at the time of the start of observation >548.02 ng/ml (AUC = 0.718, p = 0.004) and after 5 days the application of additional immunotropic therapy >443.55 ng/ml (AUC = 0.736, p = 0.026). Мета роботи – з’ясувати роль клінічних та імунологічних параметрів у прогнозуванні ефективності додаткової імунотропної терапії в кисневозалежних хворих на коронавірусну хворобу COVID-19. Матеріали та методи. Обстежили 79 кисневозалежних хворих на COVID-19, які отримали додаткову терапію тоцилізумабом, відповідно до чинних протоколів. Пацієнтів поділили на групи: I – 39 осіб, які одужали; II – 40 хворих із летальним наслідком. Методом імуноферментного аналізу в сироватці крові хворих та осіб контрольної групи визначали вміст феритину (Monobind Inc., USA), інтерлейкіну (IL) IL-2 (Elabscience, USA), IL-6 (Invitrogen, Austria), моноцитарного хемотактичного протеїну-1 (MCP-1) (Elabscience, USA). Статистично результати опрацювали в Statistica 13 for Windows (StatSoft Inc., ліцензія № JPZ804I382130ARCN10-J). Результати. Встановлено межові рівні імунологічних параметрів на різних етапах спостереження, що мають прогностичне значення щодо ризику летального наслідку COVID-19. Через 5 діб після введення тоцилізумабу збереження показника абсолютної кількості лімфоцитів крові ≤1,2 × 109/л (AUC = 0,631, p = 0,039), рівня CRP >67,5 mg/l (AUC = 0,670, p = 0,020), IL-2 >309,45 pg/ml (AUC = 0,761, p = 0,013), IL-6 >4,66 pg/ml (AUC = 0,871, p < 0,001) свідчило про високу ймовірність настання летального наслідку хвороби в пацієнтів із COVID-19. Аналіз діагностичної значущості феритину показав інформативність рівня його підвищення і на початку спостереження (>548,02 ng/ml; AUC = 0,718, p = 0,004), і через 5 діб від застосування додаткової імунотропної терапії (>443,55 ng/ml; AUC = 0,736, p = 0,026).
Роль клінічних та імунологічних параметрів у прогнозуванні ефективності додаткової імунотропної терапії в кисневозалежних хворих на коронавірусну хворобу COVID-19
Riabokon O. V. - ORCID ID: 0000-0002-7394-4649; Cherkaskyi V. V. - ORCID ID: 0000-0003-2959-8803; Riabokon Yu. Yu. - ORCID ID: 0000-0002-2273-8511.
Keywords: coronavirus disease; COVID-19; viral infection; oxygen dependence; immunology; cytokines; clinic; diagnosis; treatment; prognosis; коронавірусна хвороба; COVID-19; вірусна інфекція; киснева залежність; імунологія; цитокіни; клініка; діагностика; лікування; прогноз